A Beginner's Guide to Special Makeup Effects : Monsters, Maniacs and More. - Payne, Christopher (Oxford : Taylor & Francis Group, 2020)
A Beginner's Guide to Special Makeup Effects: Monsters, Maniacs and More is an introduction to special effects makeup using cost-effective tools and materials that can be found in local stores.
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Introduction -- Preface -- Tools and Materials -- Meet the Models -- Section 1: Simple Makeup -- Chapter 1 Pirate -- Chapter 2 Highlight and Shadow -- Chapter 3 Vampire -- Chapter 4 Ghost -- Chapter 5 Robot -- Chapter 6 Basic Burn -- Chapter 7 Basic Zombie -- Chapter 8 Plague -- Chapter 9 Witch -- Section 2: Advanced Materials and Techniques -- Chapter 10 Fangs and Claws -- Chapter 11 Teeth -- Chapter 12 Blood -- Chapter 13 Bald Caps -- Chapter 14 Blocking Out Hair -- Chapter 15 Skin Textures -- Chapter 16 Cotton and Latex -- Chapter 17 Wounds and Injuries -- Chapter 18 Hair and Stubble -- Chapter 19 Making Basic Prosthetics -- Chapter 20 Character Design -- Section 3: Advanced Makeup -- Chapter 21 The Champ -- Chapter 22 Grim Reaper -- Chapter 23 Giggles -- Chapter 24 Severe Burn -- Chapter 25 Goblin -- Chapter 26 The Creature -- Chapter 27 Advanced Zombie -- Chapter 28 Pirate . . . Again -- Appendix 1 Skincare and Sanitation -- Appendix 2 Glossary -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Theatrical prosthetic makeup-Handbooks, manuals, etc; Electronic books